Drosophila damage-specific DNA-binding protein 1 (D-DDB1) is controlled by the DRE/DREF system. - Takata, K.; Ishikawa, G.; Hirose, F.; Sakaguchi, K. (Nucleic Acids Research, 2002)
We succeeded in cloning the gene, termed d-ddb1, for a Drosophila homolog of the p127 subunit of the human damage-specific DNA-binding protein, thought to recognize (6-4) photoproducts and related structures. In Drosophila, the gene product (D-DDB1) also appeared to play a role as a repair factor, d-ddb1 knockout Kc cells generated with a RNAi method being sensitive to UV. In addition, UV or methyl methanesulfonate treatment increased d-ddb1 transcripts. However, we found that the gene is controlled by the DRE/DREF system, which is generally responsible for activating the promoters of proliferation-related genes. Moreover, during Drosophila development, the transcription of d-ddb1 changed greatly, with the highest levels in unfertilized eggs, indicating that external injury to DNA is not essential to D-DDB1 function. Interestingly, as with UV irradiation-induced transfer of D-DDB1 to the nucleus from the cytoplasm, during spermatogenesis the protein transiently shifted from one cell compartment to the other. The results indicate that D-DDB1 not only contributes to the DNA repair system, but also has a role in cell proliferation and development.